The reduction of work in progress between process in strut production line of a manufacturing factory - Nur Nadiah, Mohammad Alwudin (2012)
In today’s competitive business world, companies require small lead times, low costs and high customer service levels to survive. Because of this, companies have become more customers focused. The result is that companies have been putting in significant effort to reduce their lead times. The purpose of this thesis was to reduce work in progress (WIP) between processes at ST (strut) production line in APM Shock Absorber Sdn Bhd. In order to achieve this, all processes that focus on three processes only which is ABW ABF, CO2 welding, and LET KHP. Some changes based on the Toyota Production System (TPS) were implemented, The results were then shown in Yamazumi chart and then the implementation were sustained in the standard operating procedure (SOP). APM Shock Absorber Sdn Bhd has more than 32 years’ experience of producing absorber for automotive part. Due to globalization and stiff competition, the reduction of WIP for each process is important so that they have a smooth production line flow and could maintain their customer satisfaction. It was found that the most appropriate method for lead time reduction was doing the visualization of current cycle time on Yamazumi chart. Another observation that was derived from the Yamazumi chart is the bottlenecks can be derived and waste at ST line can be eliminated by having Kaizen activity such as reduce waiting time and position the machine comfortably for the operator doing their process. Some other recommended changes based on applying TPS are reduction of work in process inventory (WIP), reduction of waiting time, stop the process to build in quality, collect more information, and implementation of the 5S methodology. By implementing these changes, the future state the of WIP can be reduce in between of the process and smooth production flow can occur.